122: Experience with Abdominal Injury: A Survey of Child Maltreatment Physicians. Issue 6 (1st June 2014) - Murray, L; Baird, B; Chauvin-Kimoff, L; MacPherson, J
Abstract: BACKGROUND: Abdominal trauma is an uncommon and poorly recognized form of child abuse associated with a high risk of mortality. Abuse is considered as a possible cause when the mechanism of the injury is poorly explained and/or there are other indicators of physical abuse. Physicians may also screen for occult abdominal injuries in the context of other signs of physical abuse, however currently no recognized guideline exists for the identification of occult inflicted abdominal injuries OBJECTIVES: The goal of this study was to describe the current practices of Canadian experts in Child Maltreatment in the assessment of abdominal injury. This information will help inform the future development of national guidelines on this topic. DESIGN/METHODS: A 21- item survey was developed and reviewed for content. The anonymous electronic survey was sent to participants in the 4th Canadian Symposium on Advanced Practices in Child Abuse Pediatrics and to the Canadian Pediatric Society (CPS) Child Maltreatment section members. The survey contained questions on demographics, experience and current practices with cases of abdominal trauma and approach to clinical scenarios. RESULTS: The survey was completed by 46 of 162 individuals (54 Symposium participants and 108 Section members) for a response rate 28.4%. Respondents were primarily pediatricians (88.1%). Cases of abdominal trauma had been assessed by 65.9% of respondents, with 76.9% of these having seen one to five cases. Cases most commonly involved injuries to the liver (n=16 [61.5%]), intestine (n=13 [50%]), spleen (n=9 [34.6%]) and pancreas (n=8 [30.8%]). Occult solid organ and intestinal injuries were identified through screening bloodwork, however mesentery/vascular injuries were not. Most physicians (97%) sometimes or always ordered screening tests for abdominal injury in cases of suspected physical abuse. The most frequently ordered tests were AST (n=38 [97.4%]), ALT (n=37 [94.9%]), amylase (n=26 [66.7%]), lipase (n=26 [66.7%]) and urinalysis (n=26 [66.7%]). Respondents were most likely (65.8%) to recommend a CT scan if suspecting a possible visceral injury, however 26.3% recommended an ultrasound. Most respondents (81.6%) favoured a national guideline on this topic, with 50% indicating that there were areas of controversy/uncertainty that created difficulty in formulating a child maltreatment opinion on cases. CONCLUSIONS: This study provides a description of the current experiences and practices in cases of abdominal injury of Canadian child maltreatment physicians. There is substantial variability in number of cases assessed, organs involved, and medical testing used in assessments. Child maltreatment pediatricians support the need for a clinical guideline on this topic.